2012
DOI: 10.1111/j.1540-6261.2012.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Carry Trades and Global Foreign Exchange Volatility

Abstract: We investigate the relation between global foreign exchange (FX) volatility risk and the cross section of excess returns arising from popular strategies that borrow in low interest rate currencies and invest in high interest rate currencies, so‐called “carry trades.” We find that high interest rate currencies are negatively related to innovations in global FX volatility, and thus deliver low returns in times of unexpected high volatility, when low interest rate currencies provide a hedge by yielding positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
518
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 773 publications
(610 citation statements)
references
References 68 publications
(128 reference statements)
47
518
2
2
Order By: Relevance
“…We can thus conclude that investors' risk aversion clearly plays an important role in the tail behaviour. This conclusion corroborates recent literature regarding the skewness and the kurtosis features characterising the currency carry trade portfolios [5,11,23].…”
Section: Remark 2 (Model Risk and Its Influence On Upside And Downsidsupporting
confidence: 81%
See 1 more Smart Citation
“…We can thus conclude that investors' risk aversion clearly plays an important role in the tail behaviour. This conclusion corroborates recent literature regarding the skewness and the kurtosis features characterising the currency carry trade portfolios [5,11,23].…”
Section: Remark 2 (Model Risk and Its Influence On Upside And Downsidsupporting
confidence: 81%
“…Our empirical analysis consists of daily exchange rate data for a set of 34 currency exchange rates relative to the USD, as in [23] We have considered daily settlement prices for each currency exchange rate as well as the daily settlement price for the associated 1 month forward contract. We utilise the same dataset (albeit starting in 1989 rather than 1983 and running up until January 2014) as studied in [20,23] in order to replicate their portfolio returns without tail dependence risk adjustments. Due to differing market closing days, e.g.…”
Section: Exchange Rate Multivariate Data Description and Currency Pormentioning
confidence: 99%
“…They relate these factors to global equity market volatility. In a similar way, Menkhoff et al (2012) found that global foreign exchange volatility risk accounts for the highest explanation of cross-sectional excess returns of carry trade portfolios and that liquidity risk also play a role in the explanation of their foreign exchange expected returns. By constructing a measure of FX global liquidity, Banti et al (2012) show that there is a link between liquidity across currencies and that liquidity risk is priced in the cross section of currency returns.…”
Section: Identification Of the Common Factorsmentioning
confidence: 67%
“…The latter is relevant in cross sectional analysis as profits from trading strategies typically depend on their risk, which may be different for several forecasters. 5 Sharpe ratios can also be linked to other studies on exchange rate models (Jordà and Taylor, 2009;Rime, Sarno, and Sojli, 2010) or carry trade strategies (Burnside, Eichenbaum, Kleshchelski, and Rebelo, 2010;Menkhoff, Sarno, Schmeling, and Schrimpf, 2011).…”
Section: Forecasting Performancementioning
confidence: 99%